FACTORS OF AFFECTING THESIS COMPLETION BY USING CHAID METHOD BASED ON GENDER - Haida Fitri; Aniswita Aniswita; Charles Charles (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2019)
Thesis as one of the requirements to obtain a bachelor degree, ideally it can be completed in one semester, but many students finish the thesis more than the allocated time. This condition is caused by many factors including gender differences, male and female students have many differences especially in the allocation of time to finish a thesis. This research aimed to find out the factors that influence the time needed to finish a thesis and the classification of these factors based on their gender. The factors observed were GPA, gender and competence of the supervisor, types of research used, source of the data and technique of the data collection. The statistical analysis used was the CHAID method. The result of this study showed that out of 387 male students who have graduated in period I to VI, it was found that the factors which influence them to finish their thesis were GPA. While for female students, out of 1150 data, three factors that influence them were major, sources of data and expertise areas of the main supervisors. Moreover, three characteristics of students who finish thesis longer than 6 months were male students with a GPA less than 3,34, female students from Islamic Education/English Department/Math Department with the source primary/ secondary data or others, and female students from guidance and couceling department by the psychologist’s/ others as main supervisor.Keywords: thesis, allocated time to finish thesis, CHAID method.